The Effect Of Work Competency And Compensation On Teachers' Organizational Commitment - Panjaitan, Birmawaslin; Ali Musri S, M.; Supriyani Siregar, Epi (International Journal of Science, Technology & Management, 2024)
Commitment to each member of the organization is very important because with a commitment, a member of the organization can be more responsible for his work. This study aims to determine: The Effect of Work Competence and Compensation on Organizational Commitment moderated by Job Satisfaction of Junior High School Teachers in Bandar Pasir Mandoge District. The population of this study was all Junior High School teachers in Bandar Pasir Mandoge District, totaling 79 teachers, while the sample taken from the entire population was 79 people by taking a census sample. Data were collected using a questionnaire filled out by respondents from teachers, then the data was processed using regression analysis. The results of the study showed that: work competence (X1) has a direct positive effect on organizational commitment (Y) shown that = 0.238 and significance> 0.05; compensation (X2) has a direct positive effect on organizational commitment (Y) shown that = 0.337 and significance> 0.05. .